(untitled) (Homoeopathy for All, 2024)
A cough is a reflex action by the body that helps clear the airways of irritants, mucus, or foreign substances. It is typically characterized by a sudden, forceful expulsion of air from the lungs, often accompanied by a distinctive sound. Coughing is a natural defense mechanism that can be triggered by various factors,including respiratory infections,irritants in the air, allergies, and underlying medical conditions. Coughing is typically initiated in response to an irritation or stimulus. This can include anything that irritates the lining of the airways, such as dust, smoke, allergens, mucus, or infectious agents like bacteria or viruses. Sensory receptors in the airway lining detect these irritants. When these receptors detect an irritant, they send signals to the brain via sensory nerves. If the brain determines that coughing is necessary to clear the airways, it activates the "cough center," located in the medulla oblongata at the base of the brain.